IDENTIFIKASI SENYAWA GARLISIN DAN KUERSETIN SEBAGAI SENYAWA ANTIMIKROBA PADA SEDIAAN BASAH DAN KERING BAWANG PUTIH (Allium sativum L.) - Yunus, Fanny Thresia; Suwondo, Ari; Martini, Martini (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Indonesian people have long used garlic as traditional medicine because it contains various chemical compounds that are beneficial to the body. In this study identification of garlicin and kuersetin compounds in garlic as an antibacterial. This study requires 500 grams of garlic each in wet preparations consist of fine garlic and garlic extract, and dry preparation consists of garlic powder. In addition, this research requires 2,1 liters of 96% ethanol. Garlic is dried at 400C with TMI Vacuum Oven and extracted at 250C. Garlic powder is made using Krisbow dry cabinet with a temperature of 1000F and a pressure of 10 Pa. Garlisin content was identified by GCMS Shimadzu TQ8030 and FTIR Perkin Elmer Spectrum Two UATR, while identification of quercetin using Shimadzu HPLC type UFLC. The result shows that the compound garlicin (C6H10S2) was found in the three samples with identical similarity levels. In addition, the three samples showed differences in kuersetin content. The highest kuersetin content was 458.729 ppm garlic extract while the lowest kuersetin content was 81.181 ppm fresh garlic. Both of these compounds have potential as antimicrobial compounds.